Synthesis and Antidepressant Activity Profile of Some Novel Benzothiazole Derivatives - Ümide Demir Özkay; Ceren Kaya; Ulviye Acar Çevik; Özgür Devrim Can (Molecules, 2017)
Within the scope of our new antidepressant drug development efforts, in this study, we synthesized eight novel benzothiazole derivatives 3a–3h. The chemical structures of the synthesized compounds were elucidated by spectroscopic methods. Test compounds were administered orally at a dose of 40 mg/kg to mice 24, 5 and 1 h before performing tail suspension, modified forced swimming, and activity cage tests. The obtained results showed that compounds 3c, 3d, 3f–3h reduced the immobility time of mice as assessed in the tail suspension test. Moreover, in the modified forced swimming tests, the same compounds significantly decreased the immobility, but increased the swimming frequencies of mice, without any alteration in the climbing frequencies. These results, similar to the results induced by the reference drug fluoxetine (20 mg/kg, po), indicated the antidepressant-like activities of the compounds 3c, 3d, 3f–3h. Owing to the fact that test compounds did not induce any significant alteration in the total number of spontaneous locomotor activities, the antidepressant-like effects of these derivatives seemed to be specific. In order to predict ADME parameters of the synthesized compounds 3a–3h, some physicochemical parameters were calculated. The ADME prediction study revealed that all synthesized compounds may possess good pharmacokinetic profiles.